PENDAMPINGAN PERANCANGAN DAN PENYUSUNAN LAPORAN KEUANGAN DENGAN APLIKASI AKUNTANSI EXCEL - Kusuma Indawati Halim (Jurnal Abdimas Bina Bangsa, 2022)
The excel accounting application allowed business users to record and process data to produce reports on the performance of business activities. Users can define special formulas to calculate and present reports either monthly, quarterly, semi-annually and annually. This application is very helpful for business users to present information accurately and quickly. The purpose of this community service is to increase the knowledge of partners regarding the excel's calculation functions and the process of preparing financial statements by utilizing the excel accounting application. The implementation of this activities begins with observations and questions and answers. The design of the excel accounting application will then be developed, mentoring activities will follow, and the evaluation of the application's outcomes will come last. The outcomes of this community activity improve the partners' understanding of excel's calculation functions and the value of business management by utilizing excel accounting applications. It is now simpler for partners to enter data while presenting financial reports in a timely and accurate manner